Deficient Neutrophil Extracellular Trap Formation in Patients Undergoing Bone Marrow Transplantation - Glenn, Jared W.; Cody, Mark J.; McManus, Meghann P.; Pulsipher, Michael A.; Schiffman, Joshua D.; Yost, Christian Con (Frontiers in Immunology, 2016)
Overwhelming infection causes significant morbidity and mortality among patients treated with bone marrow transplantation (BMT) for primary immune deficiencies, syndromes of bone marrow failure, or cancer. The polymorphonuclear leukocyte (PMN; neutrophil) is the first responder to microbial invasion and acts within the innate immune system to contain and clear infections. PMNs contain, and possibly clear, infections in part by forming neutrophil extracellular traps (NET). NETs are extensive lattices of extracellular DNA and decondensed chromatin decorated with anti-microbial proteins and degradative enzymes such as histones, myeloperoxidase, and neutrophil elastase (NE). They trap and contain microbes including bacteria and fungi, and may directly affect extracellular microbial killing. Whether or not deficient NET formation contributes to the increased risk for overwhelming infection in patients undergoing BMT remains incompletely characterized, especially in the pediatric population. We examined NET formation in vitro in PMNs isolated from 24 patients who had undergone BMT for 13 different clinical indications. For these 24 study participants, the median age was 7 years. For 6 of the 24 patients, we examined NET formation by PMNs isolated from serial, peripheral blood samples drawn at 3 different clinical time points: pre-BMT, pre-engraftment, and post-engraftment. We found decreased NET formation by PMNs isolated from patients prior to BMT and during the pre-engraftment and post-engraftment phases, with decreased NET formation compared to healthy control PMNs detected even out to 199 days after their BMT. This decrease in NET formation after BMT did not result from neutrophil developmental immaturity as we demonstrated that > 80% of the PMNs tested using flow cytometry expressed both CD10 and CD16 as markers of terminal differentiation along the neutrophilic lineage. These pilot study results mandate further exploration regarding the mechanism(s) or factor(s) regulating NET formation by PMNs in patients at risk for overwhelming infection following BMT.